Measuring the Stability of Iraqi Banking System according to Basel III - محسن مها مزهر (Journal of Economics and Administrative Sciences, 2017)
Banking reforms in many countries have focused on the efficiency enhance of the banking sector, including Iraq, in terms of indicative steps based on recommendations, policies and standards developed by international organizations, foremost of which are Basel III. In this paper, it has tried to highlight the reforms in Basel III and the impact of these reforms on the stability of the banking system in Iraq. As the research derives its importance from the idea that the sound banking system consists of a group of banks capable of employing their assets and obligations efficiently in financial intermediation and enjoying financial solvency. The stability of the banking system is an important factor in achieving the leading role of the banking sector in achieving economic and social development. Comprehensive, attracting foreign capital and preserving national capital. The study concluded with a set of conclusions and recommendations aimed at rehabilitating Iraq’s commercial banks so that they can meet the requirements of Basel III so as to confirm their position in the global banking system and benefit from their competitive advantage to gain their share of the local and international banking industry.